A dataset of cetacean occurrences in the Eastern North Atlantic - Correia, Ana M. (2019)
The CETUS project is a cetacean monitoring program that takes advantage of cargo ships to undertake survey routes between Continental Portugal, Macaronesian archipelagos and West Africa. From 2012 to 2017, over 50 volunteers participated in the program, actively surveying more than 124.000 km, mostly beyond national jurisdictions in the high seas, for which little or no previous data existed. In total, the collection comprises 3058 georeferenced transect lines and 8913 positions, which are associated with 2833 cetacean sightings, 362 occurrences of other pelagic megafauna, 5260 estimates of marine traffic and 8887 weather observations. This dataset may provide new insights into the distribution of marine mammals in the Eastern North Atlantic and was published following the OBIS-ENV-DATA format (with the most recent biodiversity data standards at the time of writing). Consequently, it may serve as a model for similar visual line transect data collections yet to be published.